Evaluation of the bioavailability and intestinal effects of milk fermented by folate producing lactic acid bacteria in a depletion/repletion mice model - Cucick, Ana Clara C. (2020)
This study aimed to evaluate the bioavailability and effects on the intestinal mucosa of a bioenriched fermented milk (BFM) prepared with folate-producing lactic acid bacteria, using a depletion/repletion BALB/c mice model. Five Streptococcus thermophilus strains were combined with Lactobacillus plantarum 16cv and the combination that resulted in the best folate production was used for preparation of BFM. The folate content in BFM, prepared under controlled conditions (pH 6.0, 42 °C, 70 rpm, 24 h), was 321.1 ± 14.1 ng/mL. Results for mice fed with BFM were compared to those fed with other diets. The BFM group presented an increase in hemoglobin, hematocrit and red blood cells, and the villi height/crypt depth ratio was similar to that of animals receiving milk supplemented with commercial folic acid. The strains were sensitive to most tested antibiotics and lacked virulence genes, indicating that consumption of BFM may be a promising alternative to increase intake of folate.